How MOOC-Takers Estimate Learning Success: Retrospective Reflection of Perceived Benefits - Svetlana Sablina (Athabasca University Press, 2018)
Massive open online courses (MOOCs) have attracted a great deal of interest in recent years as a new learning technology. Since MOOCs inception, only limited research has been carried out to address how learners perceive success in MOOCs after course completion.  The aim of this study was to investigate the perceived benefits as the measurement of learning success.  Narrative interviews were conducted with 30 Russian-speaking learners who completed at least one MOOC in full.  By employing text analysis of interview transcripts, we revealed the authentic voices of participants and gained deeper understanding of learners' perceived benefits based on retrospective reflection. The findings of the study indicate that after finishing MOOCs, learners have received tangible and intangible benefits that in general justified their expectations.  University-affiliated students, as well as working professionals, recognized the complementarity of MOOCs, but their assessments were limited to educational tracks. We discovered that taking MOOCs often coincided with the time when an individual was planning to change career, education, or life tracks.  The results of the study and their implications are further discussed, together with practical suggestions for MOOC providers.